A interdisciplinaridade no ensino superior: um estudo de caso do projeto interdisciplinar da Faculdade Batista Brasileira, especificamente no curso de Administração de Empresas - Miranda, Fernando Antônio Nogueira (2014)
This paper is a result of a research project which seeks to present the contribution of interdisciplinarity to the development of knowledge in the Business Administration Program of the Faculdade Batista Brasileira [Brazilian Baptist College], discussing its contribution to the cultural enrichment of its students and to the integrated education of the future administrator. Its title is presented as: The interdisciplinarity of higher learning: a case study of the interdisciplinary project of the Faculdade Batista Brasileira, specifically the Business Administration Program. It was developed having as its methodology exploratory bibliographic research, studies of documents and the case study. Its theoretical referential support in the area is with the goal of presenting and discussing the guiding aspects of interdisciplinarity and its quest for overcoming the fragmentation of knowledge. It seeks to analyze how this interdisciplinary methodology is being used in the Business Administration Program of the Faculdade Batista Brasileira, through analyzing the projects developed during the program by the students and professors. Besides this it also deals with each one of the projects developed during the semester in the program, analyzing them from an interdisciplinary perspective, demonstrating the ever greater possibility of constructing new paths of knowledge. The work ends with the comprehension that interdisciplinary studies can generate new investigations and new ideas, depending, as well, on the advancement itself of the disciplines which make up these studies.